Gis-Based Support System for Tactical Timber Harvest Planning: Design and Development - Cabral, Judibal Carvalho (2000)
The high costs of timber harvesting and forest road construction warrant extensive planning of harvest blocks and forest road network layout. The integration of these efforts in the overall management decision making process will result in more efficient timber harvesting operations. Traditionally, harvest planners have relied in personal experience to guide them through this planning process. However, the harvest planner may not be able to utilize these traditional planning techniques when dealing with large areas due to the increased data demands of the planning process. This study describes a terrain classification method and the development of a Decision Support System CDSS) known as "MERANTI" for short-term harvest planning that combines the data handling, storage, and retrieval advantages of a geographic information system with the decision modelling capabilities of heuristic programming. The terrain classification system characterizes the terrain of forested areas in eastern part of Malaysia in terms of slope and ground conditions. The DSS consists of three major components: the geographic information system, a library of decision models, and a graphics interface. The geographic information system contains information on timber volume, roads and the terrain classification developed as a part of this study. The model library consists of three decision models: a heuristic programming to select blocks for harvest and a minimum spanning tree/shortest path module to determine the location of roads to access harvested blocks. The graphics interface provides a linking mechanism between the geographic information system, the decision model, and the harvest planner. The prototype spatial decision support system (MERANTI) developed in this study provide the harvest planner with an efficient means of evaluating the large amount of data required for automatically selecting blocks for harvest and determining preliminary forest road locations. The results demonstrated that by using "MERANTI'. decision support tools during a timber harvest planning process, the effectiveness of decision making could be improved. The findings of the study will help refine the tropical hill Dipterocarp timber harvesting system and planning and could provide guidelines for future GIS-based support system development